The Effect of Self-Control on Learning Discipline in Grade X Students of MAN 5 Ciamis 2026 - Ali Kuswali (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Learning discipline is an important aspect in supporting student success in school. However, in reality, there are still many students who display undisciplined behavior, such as procrastinating on assignments, lack of focus in learning or during lessons, playing with cell phones, talking with friends, and not complying with academic regulations. The purpose of this study was to determine the level of self-control, the level of learning discipline, and the effect of self-control on the learning discipline of class X students of MAN 5 Ciamis. This approach used a quantitative approach using the associative method. The population of 130 class X students of MAN 5 Ciamis was determined at 98 students using the Slovin formula and simple random sampling techniques. The instrument used was a questionnaire using a Likert scale scoring. Data analysis uses validity test, reliability test, descriptive analysis, linearity test, Person Product Moment correlation, and simple linear regression. Based on the results of the data analysis that has been done, the average score of student self-control is 46.94. The average discipline score is 49.11. The correlation results show a strong relationship between self-control and learning discipline with a value of r = 0.6808 and a significance of 0.000. The results of simple linear regression show the equation Y = 18.236 + 0.584X with an R Square value of 0.4635, which means the influence of self-control is 46.35% on student learning discipline. Based on these results, it is concluded that self-control has a positive and significant effect on learning discipline in class X students of MAN 5 Ciamis.